Preparation method of flexible self-repairing super-hydrophobic capsule modified coating
Through the formal preparation of the flexible polychor PDMS capsules of the load nano -PTFE particles to build a full organic ultra -hydrophobic capsule coating, it solves the problem that the existing coating is difficult to take into account in terms of mechanical stability, chemical stability, and flexibility. High -performance applications in the environment.
Patent Information
- Application Number
- CN202411634662.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
AI Technical Summary
Existing superhydrophobic coatings are difficult to balance mechanical stability, chemical stability and flexibility, and their performance deteriorates in extreme environments.
Prepare flexible multi -porous PDMS capsules by suspended polymerization, load nano -PTFE particles, and build a full organic ultra -hydrophobic capsule coating. The coating has self -repair ability when it is damaged, and can maintain excellent hydrophilicity in extreme environments.
The chemistry and mechanical stability of the full organic flexible ultra -water coating are implemented, and the low ice adhesion force is shown in the field of anti -ice prevention, which significantly enhances the application prospects of ultra -hydrophobic coating in the engineering field.
Smart Images

Figure CN119371874A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of super hydrophobic materials, and specifically relates to a method for preparing a flexible self-repairing super hydrophobic capsule modified coating. Background Art
[0002] Hydrophobic surfaces are widely present in nature. Lotus leaves are a classic representative for their characteristic of "coming out of the mud without getting stained". Their surfaces have low rolling angles and high contact angles, which have attracted wide attention from the scientific research community. Scientists have designed and prepared a variety of super-hydrophobic coatings based on the microstructure and surface functions of lotus leaves. These coatings have been used in the fields of self-cleaning, oil-water separation, anti-corrosion and anti-icing. The preparation of super-hydrophobic surfaces can be carried out from both macroscopic and microscopic levels: the macroscopic level focuses on the construction of surface microstructures, and a surface with special textures and shapes is formed through specific process methods to achieve a hydrophobic effect; the microscopic level focuses on reducing the surface energy level by selecting low surface energy materials, thereby enhancing its hydrophobicity. Researchers have adopted a variety of methods to construct super-hydrophobic surfaces, including template method, sol-gel method, deposition method, laser etching method and chemical etching method. These methods provide diverse paths for the design and preparation of super-hydrophobic surfaces and promote the development and application of related technologies.
[0003] Among the many methods for preparing superhydrophobic coatings, the one-step spraying or brushing method is suitable for large-area engineering applications due to its simplicity. The literature (Nature Mater 17,355–360) proposed the concept of an all-organic coating, which exhibits excellent chemical stability, flexibility and certain mechanical stability. Recently, the literature (Nat Commun 14,5953(2023)) proposed the concept of a superhydrophobic unit cell, which enhanced the mechanical stability of the coating by introducing diatomaceous earth-loaded nanoparticles. If the all-organic component is combined with the unit cell concept, it is expected to achieve an excellent balance of chemical stability, mechanical stability and flexibility, thereby further improving the performance of superhydrophobic coatings. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a flexible self-repairing super-hydrophobic capsule modified coating.
[0005] A method for preparing a flexible self-repairing super-hydrophobic capsule modified coating is carried out according to the following steps:
[0006] S1. Place liquid PDMS system A, porogen system B and catalyst C in a three-necked flask, stir for 30-40 seconds, add dispersed system D, cross-link, filter, wash and dry to obtain a porous PDMS capsule shell E;
[0007] S2, placing the porous PDMS capsule E, the catalyst F and the mixed solution G in a beaker, stirring at a speed of 800-1000 r / min for 2-3 hours, filtering, washing, drying and grinding to obtain a partially amino-modified flexible capsule shell H;
[0008] S3, adding polytetrafluoroethylene (PTFE) with a particle size of 200nm / 5um, perfluorosilicone (FAS), and flexible capsule shell H into deionized water containing 40-45wt% ethyl acetate, and magnetically stirring for 36-42h in an oil bath heated at 50-60°C, to obtain PDMS flexible capsules after drying, adding the flexible capsules into ethyl acetate, stirring at 500-600r / min for 10-15min, and oscillating in an ultrasonic cleaner for 2-3min to obtain capsule dispersion J;
[0009] S4, slowly adding the capsule dispersion J to the resin dispersion K being stirred at a speed of 500-600 r / min, magnetically stirring at a speed of 500-600 r / min for 1-2 h, adding the curing agent L, and magnetically stirring at 500-600 r / min for 5-10 min to obtain a super hydrophobic coating, recorded as M;
[0010] S5. Select a coating process, evenly apply M to the substrate, and dry it in an oven at 60-80°C for 6-8h to form a flexible repairable super-hydrophobic coating.
[0011] The preparation method of the liquid PDMS system A is as follows: 7-8 g of polydimethylsiloxane, 8-9 g of silicone oil and 8-9 g of ethyl acetate are placed in a beaker, and ultrasonically dispersed for 10-15 minutes.
[0012] The preparation method of the porogen system B is as follows: 1-2 g of polymethyl methacrylate (PMMA) particles and 4-5 g of ethyl acetate are placed in a beaker, and the mixture is placed in an ultrasonic washer and vibrated for 30-40 seconds.
[0013] The catalyst C is one or more of Pt, Fe and Ag.
[0014] The preparation method of the dispersion system D is as follows: 300g-400g of deionized water, 4-5g of Tween-20, and 0.4-0.5g of Span-80 are placed in a beaker, and stirred at a speed of 500-600r / min for 20-30min to mix them evenly.
[0015] The catalyst F is one or more of triethanolamine (TEA), diethanolamine (DEA) or dibutyltin dilaurate (DBTDL).
[0016] The preparation method of the mixed solution G is as follows: silane coupling agent KH550, deionized water and anhydrous ethanol are mixed in a mass ratio of 1:5:44, and stirred at a speed of 300-400 r / min for 3-5 min.
[0017] The resin dispersion K is prepared by adding 10-12 g of epoxy resin or 10-12 g of room temperature vulcanized silicone rubber (RTV) into 15-20 g of ethyl acetate, stirring at 1000-1200 r / min for 10-12 min, and oscillating in an ultrasonic cleaner for 2-3 min.
[0018] The curing agent L is an epoxy curing agent and / or a polyamide curing agent. The epoxy curing agent is one or more of DMP-30, D230, T403, D400, and 593 curing agents; the polyamide curing agent is one or more of polyamide 650, polyamide 651, PA902, PA901, and Ancamide 2741.
[0019] The coating process is dipping, rolling, spraying or wire rod coating.
[0020] Beneficial effects of the present invention: The present invention successfully prepares a flexible porous PDMS capsule by suspension polymerization, and the capsule can load nano PTFE particles to construct an all-organic super-hydrophobic capsule. The new capsule is like a solid protective barrier, effectively resisting damage from wear, corrosion and external loads. When damaged, the high elasticity of the capsule allows it to quickly return to its original state. At the same time, the PTFE particles inside the capsule will be released to fill small defects. Even in extreme environments, the coating can still maintain excellent super-hydrophobicity and show low ice adhesion in the field of anti-icing. The all-organic flexible super-hydrophobic capsule coating is easy to construct and has excellent mechanical and chemical stability, which will greatly expand the application prospects of super-hydrophobic coatings in the engineering field. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is an electron microscope scanning image of the ordered microstructure of Example 1.
[0022] Figure 2 This is an electron microscope scanning image of the super-hydrophobic anti-icing coating reinforced with an ordered micron structure in Example 1.
[0023] Figure 3 Figure 1 is a diagram of the Taber wear quantitative test device.
[0024] Figure 4 The change of water contact angle of different coatings during Taber wear under 1000g load.
[0025] Figure 5 The change of water roll-off angle of different coatings during Taber wear under 1000g load.
[0026] Figure 6 The variation of ice adhesion strength of Example 1 during cyclic freezing / deicing.
[0027] Figure 7 Water droplet contact angles of different coatings under different high-speed water flow impacts.
[0028] Figure 8 Rolling angle of water droplets on different coatings under the impact of different high-speed water flows.
[0029] Fig. 9 Stress-strain curves of different coatings. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] Example 1
[0032] A method for preparing a flexible self-repairing super-hydrophobic capsule modified coating is carried out according to the following steps:
[0033] S1. 7g PDMS, 8g silicone oil and 8g ethyl acetate were placed in a beaker and ultrasonically dispersed for 10min. The resulting solution was recorded as A. 1g PMMA particles and 4g ethyl acetate were placed in a beaker and oscillated in an ultrasonic washer for 30s. The resulting solution was recorded as B. 300g deionized water, 4g Tween-20 and 0.4g Span-80 were placed in a beaker and stirred at 500r / min for 20min. The resulting solution was recorded as D. A, B and catalyst Pt were added to a three-necked flask and rapidly stirred for 30s. D was then added. After cross-linking, filtration, washing and drying, a porous PDMS capsule shell was obtained.
[0034] S2. Prepare a mixed solution of silane coupling agent KH550: deionized water: anhydrous ethanol in a mass ratio of 1:5:44, stir at 300 r / min for 3 min, and the resulting solution is recorded as G; put 20 parts of porous PDMS capsule shells and 0.3 parts of DBTDL into solution G, stir at 800 r / min for 2 h, filter, wash, dry and grind to obtain a partially amino-modified flexible capsule shell;
[0035] S3, adding 32g of PTFE with a particle size of 200nm, 15ml of perfluorosilicone (FAS), and 16g of partially amino-modified flexible capsule shell into 40wt% ethyl acetate in deionized water, heating in an oil bath at 50°C with magnetic stirring for 36h, and obtaining PDMS flexible capsules after drying;
[0036] S4, 6g PDMS flexible capsules were added to 15g ethyl acetate, stirred at 500r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as J; 10g epoxy resin was added to 15g ethyl acetate, stirred at 1000r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as K; Solution J was slowly added to Solution K being stirred at a rate of 500r / min, then stirred at a speed of 500r / min for 1h, epoxy curing agent DMP-30 was added, and super hydrophobic coating was obtained by magnetic stirring at 500r / min for 5min;
[0037] S5. Select a spraying process to evenly spray the super-hydrophobic coating onto the substrate, and dry it in an oven at 60° C. for 8 h to form a flexible and repairable super-hydrophobic coating.
[0038] The electron microscope scanning image of the ordered microstructure of the coating prepared in this embodiment is as follows: Figure 1 As shown, the electron microscope scanning image of the super hydrophobic anti-icing coating strengthened by the ordered microstructure is shown in Figure 2 shown.
[0039] Example 2
[0040] A method for preparing a super-hydrophobic anti-icing coating with an ordered micron structure is carried out according to the following steps:
[0041] S1. 7g PDMS, 8g silicone oil and 8g ethyl acetate were placed in a beaker and ultrasonically dispersed for 10min. The resulting solution was recorded as A. 1g PMMA particles and 4g ethyl acetate were placed in a beaker and oscillated in an ultrasonic washer for 30s. The resulting solution was recorded as B. 300g deionized water, 4g Tween-20 and 0.4g Span-80 were placed in a beaker and stirred at 500r / min for 20min. The resulting solution was recorded as D. A, B and catalyst Pt were added to a three-necked flask and rapidly stirred for 30s. D was then added. After cross-linking, filtration, washing and drying, a porous PDMS capsule shell was obtained.
[0042] S2. Prepare a mixed solution of silane coupling agent KH550: deionized water: anhydrous ethanol in a mass ratio of 1:5:44, stir at 300 r / min for 3 min, and the resulting solution is recorded as G; put 20 parts of porous PDMS capsule shells and 0.3 parts of DBTDL into solution G, stir at 800 r / min for 2 h, filter, wash, dry and grind to obtain a partially amino-modified flexible capsule shell;
[0043] S3, adding 32g of PTFE with a particle size of 200nm, 15ml of perfluorosilicone (FAS), and 16g of partially amino-modified flexible capsule shell into 40wt% ethyl acetate in deionized water, heating in an oil bath at 50°C with magnetic stirring for 36h, and obtaining PDMS flexible capsules after drying;
[0044] S4, 6g PDMS flexible capsules were added to 15g ethyl acetate, stirred at 500r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as J; 10g RTV was added to 15g ethyl acetate, stirred at 1000r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as K; Solution J was slowly added to Solution K being stirred at a rate of 500r / min, then stirred at a speed of 500r / min for 1h, epoxy curing agent polyamide 650 was added, and super hydrophobic coating was obtained by magnetic stirring at 500r / min for 5min;
[0045] S5. Select a spraying process to evenly spray the super-hydrophobic coating onto the substrate, and dry it in an oven at 60° C. for 8 h to form a flexible and repairable super-hydrophobic coating.
[0046] Control group 1
[0047] S1. 7g PDMS, 8g silicone oil and 8g ethyl acetate were placed in a beaker and ultrasonically dispersed for 10min. The resulting solution was recorded as A. 1g PMMA particles and 4g ethyl acetate were placed in a beaker and oscillated in an ultrasonic washer for 30s. The resulting solution was recorded as B. 300g deionized water, 4g Tween-20 and 0.4g Span-80 were placed in a beaker and stirred at 500r / min for 20min. The resulting solution was recorded as D. A, B and catalyst Pt were added to a three-necked flask and rapidly stirred for 30s. D was then added. After cross-linking, filtration, washing and drying, a porous PDMS capsule shell was obtained.
[0048] S2. Prepare a mixed solution of silane coupling agent KH550: deionized water: anhydrous ethanol in a mass ratio of 1:5:44, stir at 300 r / min for 3 min, and the resulting solution is recorded as G; put 20 parts of porous PDMS capsule shells and 0.3 parts of DBTDL into solution G, stir at 800 r / min for 2 h, filter, wash, dry and grind to obtain a partially amino-modified flexible capsule shell;
[0049] S3, 6g of modified flexible capsule shell was added to 15g of ethyl acetate, stirred at 500r / min for 10min, and vibrated in an ultrasonic washer for 2min, and the resulting solution was recorded as J; 10g of epoxy resin was added to 15g of ethyl acetate, stirred at 1000r / min for 10min, and vibrated in an ultrasonic washer for 2min, and the resulting solution was recorded as K. Solution J was slowly added to solution K being stirred at a rate of 500r / min, then stirred at a speed of 500r / min for 1h, epoxy curing agent DMP-30 was added, and super hydrophobic coating was obtained by magnetic stirring at 500r / min for 5min;
[0050] S4. Select a spraying process, spray the super-hydrophobic coating evenly onto the substrate, and dry it in a 60° C. oven for 8 hours to form a flexible and repairable super-hydrophobic coating.
[0051] Control group 2
[0052] S1. Add 32 g of PTFE with a particle size of 200 nm, 15 ml of perfluorosilicone (FAS), and 16 g of PTFE with a particle size of 5 μm into 40 wt% ethyl acetate in deionized water, and stir magnetically for 36 h in an oil bath at 50° C., and obtain flexible capsules after drying.
[0053] S2, 6g modified flexible capsule shell was added to 15g ethyl acetate, stirred at 500r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as J; 10g epoxy resin was added to 15g ethyl acetate, stirred at 1000r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as K; Solution J was slowly added to Solution K being stirred at a rate of 500r / min, then stirred at a speed of 500r / min for 1h, epoxy curing agent DMP-30 was added, and super hydrophobic coating was obtained by magnetic stirring at 500r / min for 5min;
[0054] S3. Select a spraying process to evenly spray the super-hydrophobic coating onto the substrate, and dry it in a 60° C. oven for 8 hours to form a flexible and repairable super-hydrophobic coating.
[0055] Control group 3
[0056] S1, adding 32g of PTFE with a particle size of 200nm and 15ml of perfluorosilicone (FAS) into 40wt% of deionized water containing ethyl acetate, heating in an oil bath at 50°C with magnetic stirring for 36h, and obtaining nano seeds after drying;
[0057] S2, 6g of nano seeds were added to 15g of ethyl acetate, stirred at 500r / min for 10min, and oscillated in an ultrasonic washer for 2min, and the resulting solution was recorded as J; 10g of epoxy resin was added to 15g of ethyl acetate, stirred at 1000r / min for 10min, and placed in an ultrasonic washer for oscillation for 2min, and the resulting solution was recorded as K; Solution J was slowly added to Solution K being stirred at a rate of 500r / min, then stirred at a speed of 500r / min for 1h, epoxy curing agent DMP-30 was added, and super-hydrophobic coating was obtained by magnetic stirring at 500r / min for 5min;
[0058] S3. Select a spraying process to evenly spray the super-hydrophobic coating onto the substrate, and dry it in a 60° C. oven for 8 hours to form a flexible and repairable super-hydrophobic coating.
[0059] Experimental Example 1
[0060] Wear resistance test: using Figure 3 The apparatus was subjected to Taber abrasion testing (ASTM D4060 standard) to evaluate the wear resistance of the coating. For all coatings (thickness ~ 4 mm), the coating was placed in a flexible fixed film and worn by a grinding wheel at 1000 g. Each rotation of the sample plate was counted as one wear cycle. During the test, the drop coating contact angle and rolling angle were measured.
[0061] When the particles are made of flexible capsules loaded with PTFE, the coating still maintains stable superhydrophobicity (contact angle greater than 150°, rolling angle less than 10°) when the friction cycle number reaches 1000 times; when the particles are single capsule shells, the superhydrophobicity of the coating begins to decline after 450 friction cycles (contact angle greater than 150°, rolling angle greater than 10°), and when the number of cycles reaches 500, it loses superhydrophobicity (contact angle less than 150°, rolling angle greater than 10°); when the particles are mixed PTFE, the material loses superhydrophobicity after 400 friction cycles (contact angle less than 150°, rolling angle greater than 10°). When the particles are single PTFE, the material loses superhydrophobicity after 350 friction cycles (contact angle less than 150°, rolling angle greater than 10°). This experiment shows that the use of flexible capsules as particles will greatly improve the wear resistance of the coating. For more specific technical data, see Figure 4 and Figure 5 .
[0062] In this experimental example, the wear resistance of the super-hydrophobic anti-icing coating reinforced with different particles was analyzed, and the wear resistance of the coatings of several common materials after the implementation of the present invention was compared. On the one hand, it provides reference and support for technical research in related fields. On the other hand, the data show that the super-hydrophobic anti-icing coating provided by the present invention has excellent wear resistance and durability. In contrast, the literature (Nature 582 (2020) 55-66) points out that the wear resistance parameter of ordinary super-hydrophobic surfaces under the same test conditions is 150 friction cycles.
[0063] Experimental Example 2
[0064] Anti-icing test: The super-hydrophobic anti-icing coating reinforced with a flexible capsule structure prepared in Example 1 was used as the experimental group to test the change in ice adhesion strength during cyclic freezing / deicing. The test was conducted in an environment with a humidity of 40% and a temperature of -10°C. When the freezing / deicing was performed within 5 times, the ice adhesion strength was less than 2.5 kPa, and was about 20 kPa at 20 times. Subsequently, the ice adhesion strength increased with the number of cycles. For more specific technical data, see Figure 6 .
[0065] It is believed that the capsule structure, like armor, enhances the ability of the coating to resist damage from freezing / de-icing loads, and the present invention has lower ice adhesion strength in cyclic freezing / de-icing. As the number of tests continues to increase, the coating structure is damaged and the ice adhesion strength increases rapidly. As a non-polar, hydrophobic material, the PDMS (polydimethylsiloxane) capsule shell has the characteristics that it is not easy to interact strongly with polar liquids such as water. The hydrophobicity of this material means that it has a weak ability to adsorb water, so in a low temperature environment, water molecules on the PDMS surface are not easy to freeze. In addition, the surface of the PTFE (polytetrafluoroethylene) seed has extremely low surface energy and hydrophobicity, which further enhances its anti-icing performance.
[0066] Experimental Example 3
[0067] High-speed water flow impact test: In practical applications, coatings will inevitably be affected by rain. We simulate the actual environment through water impact experiments. Use a high-speed tap water jet to directly impact the coating surface to simulate the impact of actual rain. The super-hydrophobic anti-icing coating reinforced with a flexible capsule structure prepared in Example 1 was used as the experimental group, and the separate self-repairing capsule shell coating, separate capsule seed coating and mixed coating were used as the control group for high-speed water flow impact experiments. It can be seen that the flexible capsule coating has excellent water impact resistance. After 30s of high-speed water flow impact, the flexible capsule coating can still maintain a contact angle of 158.6° and a rolling angle of 5.6°. The control group loses its hydrophobicity when impacted by a low-speed water flow. For more specific technical data, see Figure 7 and Figure 8When water flows into the coating surface, the protective film formed by the super-hydrophobicity will bounce off the water column as a whole, and the water column will turn into many tiny water droplets and "scatter and escape". After the water flow impact ends, the coating surface still maintains super high super-hydrophobicity.
[0068] Experimental Example 4
[0069] Tensile test: The fracture strength of the coating body is evaluated by material tensile test according to ASTM D2370 standard. The sample is in the shape of a standard dumbbell, with a thickness of 5 mm, a width of 12 mm in the narrow area, and a length of 50 mm. The sample is fixed on a ZQ-990L tensile testing machine and stretched until the sample breaks, and a stress-strain curve is obtained, in which the stress when the fracture occurs is defined as the fracture strength.
[0070] By analyzing the stress-strain curves of different particle coatings, the reinforcing effect of the capsules on the coating can be intuitively observed. The experimental results show that the fracture strength of the capsule shell coating alone is higher than that of the resin, which indicates that the capsules play a reinforcing role in the coating. However, the fracture strength of this coating is lower than that of the material fully filled with the capsule coating. This is because the capsule shell coating alone is not filled with particles, which easily forms pores and loose areas in the coating, thereby reducing the overall fracture strength of the coating. The strain of the capsule coating reached 46.7%, while the strain of the mixed seed coating was only 22.4%, which means that the elongation of the capsule coating increased by 108.5% and the elastic deformation increased by 113.1%. For more specific technical data, please see Fig. 9 This performance improvement is attributed to the excellent elastic properties of the capsule shell, which endows the coating with excellent mechanical flexibility. At the same time, the appearance of cracks on the capsule surface is accompanied by the appearance of nanoparticles, which is because the capsule seeds are released under the action of tensile force. The release of seeds not only enhances the superhydrophobicity of the coating, but also further improves the overall performance of the coating.
[0071] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a flexible self-repairing super-hydrophobic capsule modified coating, characterized in that: Follow these steps: S1. Place liquid PDMS system A, porogen system B and catalyst C in a three-necked flask, stir for 30-40 seconds, add dispersed system D, cross-link, filter, wash and dry to obtain a porous PDMS capsule shell E; S2, placing the porous PDMS capsule E, the catalyst F and the mixed solution G in a beaker, stirring at a speed of 800-1000 r / min for 2-3 hours, filtering, washing, drying and grinding to obtain a partially amino-modified flexible capsule shell H; S3, adding polytetrafluoroethylene with a particle size of 200nm / 5um, perfluorosilicone, and flexible capsule shell H into deionized water containing 40-45wt% ethyl acetate, and magnetically stirring for 36-42h in an oil bath heated at 50-60°C, to obtain PDMS flexible capsules after drying, adding the flexible capsules into ethyl acetate, stirring at 500-600r / min for 10-15min, and oscillating in an ultrasonic washer for 2-3min to obtain capsule dispersion J; S4, slowly adding the capsule dispersion J to the resin dispersion K being stirred at a speed of 500-600 r / min, magnetically stirring at a speed of 500-600 r / min for 1-2 h, adding the curing agent L, and magnetically stirring at 500-600 r / min for 5-10 min to obtain a super hydrophobic coating, recorded as M; S5. Select a coating process, evenly apply M to the substrate, and dry it in an oven at 60-80°C for 6-8h to form a flexible repairable super-hydrophobic coating.
2. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The preparation method of the liquid PDMS system A is as follows: 7-8 g of polydimethylsiloxane, 8-9 g of silicone oil and 8-9 g of ethyl acetate are placed in a beaker, and ultrasonically dispersed for 10-15 minutes.
3. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The preparation method of the porogen system B is as follows: 1-2 g of polymethyl methacrylate particles and 4-5 g of ethyl acetate are placed in a beaker, and the beaker is placed in an ultrasonic washer for oscillation for 30-40 seconds.
4. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The catalyst C is one or more of Pt, Fe and Ag.
5. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The preparation method of the dispersion system D is as follows: 300g-400g of deionized water, 4-5g of Tween-20, and 0.4-0.5g of Span-80 are placed in a beaker, and stirred at a speed of 500-600r / min for 20-30min to mix them evenly.
6. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The catalyst F is one or more of triethanolamine, diethanolamine or dibutyltin dilaurate.
7. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The preparation method of the mixed solution G is: silane coupling agent KH550, deionized water and anhydrous ethanol are mixed in a mass ratio of 1:5:44, and stirred at a speed of 300-400 r / min for 3-5 minutes.
8. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The resin dispersion K is prepared by adding 10-12 g of epoxy resin or 10-12 g of room temperature vulcanized silicone rubber into 15-20 g of ethyl acetate, stirring at 1000-1200 r / min for 10-12 min, and oscillating in an ultrasonic cleaner for 2-3 min.
9. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The curing agent L is an epoxy curing agent and / or a polyamide curing agent.
10. The method for preparing the flexible self-repairing super-hydrophobic capsule modified coating according to claim 1, characterized in that: The coating process is dipping, rolling, spraying or wire rod coating.